1985
DOI: 10.3758/bf03202878
|View full text |Cite
|
Sign up to set email alerts
|

Infants’ sensitivity to familiar size: The effect of memory on spatial perception

Abstract: Two experiments investigated infants' sensitivity to familiar size as information for the distances of objects with which they had had only brief experience. Each experiment had two phases: a familiarization phase and a test phase. During the familiarization phase, the infant played with a pair of different-sized objects for 10 min. During the test phase, a pair of objects, identical to those seen in the familiarization phase but now equal in size, were presented to the infant at a fixed distance under monocul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
4

Year Published

1985
1985
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 43 publications
(59 reference statements)
4
39
4
Order By: Relevance
“…Seven-month-old infants perceive the spatial layout depicted in Ames's (1951) trapezoidal window illusion, an illusion created by several pictorial depth cues (Kaufmann, Maland, & Yonas, 1981;Yonas, Cleaves, & Pettersen, 1978), and they respond appropriately to the depth cues of familiar size (Granrud, Haake, & Yonas, 1985;Yonas, Pettersen, & Granrud, 1982), relative size (yonas, Granrud, & Pettersen, 1985), and interposition . Five-month-olds, in contrast, have not been found to be sensitive to any of these depth cues (for a review of these studies, see .…”
Section: Resultsmentioning
confidence: 99%
“…Seven-month-old infants perceive the spatial layout depicted in Ames's (1951) trapezoidal window illusion, an illusion created by several pictorial depth cues (Kaufmann, Maland, & Yonas, 1981;Yonas, Cleaves, & Pettersen, 1978), and they respond appropriately to the depth cues of familiar size (Granrud, Haake, & Yonas, 1985;Yonas, Pettersen, & Granrud, 1982), relative size (yonas, Granrud, & Pettersen, 1985), and interposition . Five-month-olds, in contrast, have not been found to be sensitive to any of these depth cues (for a review of these studies, see .…”
Section: Resultsmentioning
confidence: 99%
“…To recognize that a nearer retinal picture takes up more space than a retinal picture further away does is important to the object-aperture relationship. Reviews of developmental size problems reveal that before six months of age infants can perceive size irrespective of distance, and compare the relationship between an object and an aperture (Piaget and Inhelder 1956;Granrud, Haake et al 1985;Slater, Mattock et al 1990;Spelke, Breinlinger et al 1992). But even if they know that the retinal images vary with distance, they are unaware of how much they vary (Piaget and Inhelder 1956), and from Study III we see that it is not until 20 months of age that children can compare sizes.…”
Section: Making a Choicementioning
confidence: 88%
“…Some researchers have found that already at one week old, infants can perceive an object's physical size (size constancy) (Slater, Mattock et al 1990). Others have found that it is not until binocular vision appears, at three months, that infants can identify objects by their physical size (Granrud, Haake et al 1985). Still others propose that infants are not able to identify objects by their size until 4½ months (McKenzie, Tootell et al 1980;Wilcox 1999).…”
mentioning
confidence: 99%
“…In two rather recent studies (Granrud, Haake, & Yonas, 1985;Yonas, Pettersen, & Granrud, 1982), it has been concluded that 7-month-old infants can use familiar size as a cue to relative distance. In the first study, photographs of faces were the familiar objects.…”
Section: Responses To the Playing Cardmentioning
confidence: 98%